Facing inflation in times of digital finance: Monetary plurality and financial repertoires in the Argentinian crisis - María Soledad Sánchez (economic sociology. perspectives and conversations, 2024)
Argentina began 2024 with the odd privilege of becoming the country with the highest inflation in the world. Although inflation has once again become a first-order global issue due to the impact on the prices of basic goods of the Covid-19 pandemic and the war in Ukraine, Argentinian inflation rates were well above the global and even regional average for the period (IMF 2023). [...] Digital investments in cryptocurrencies and financial instruments such as stocks, bonds, and novel digital accounts linked to money market funds started to be part of the financial repertoires of many Argentines, making the ways to cope with inflation more complex.
Keywords: 300